PROBLEM „ISTOTY” PRAWA PODSTAWOWEGO W PERSPEKTYWIE KLASYCZNYCH TEORII PRAWA PODMIOTOWEGO - Stępkowski, Aleksander (Zeszyty Prawnicze, 2016)
the “eSSential core” oF FundaMental riGhtS in the liGht oF the claSSical riGhtS theorieS Summary This paper addresses the issue of fundamental rights as subjective rights of a specific kind, namely those which are granted by constitutional provisions. The author focuses on the protection of the “essential core” of fundamental rights. This concept serves as a point of departure for a broader analysis of the language in which the Polish Constitutional Court has been describing the construction of fundamental rights in terms of two basic theories of subjective rights formulated in the 19thcentury civil law theory. In conclusion the author points out that the Polish Constitutional Court has been using expressions peculiar to both theories of subjective rights. Each of the theories has its own specific area, in which it provides a better description of those functions of subjective rights which are not easy to describe in terms of the other theory. The will theory is much better at describing the political dimension of public life (which is particularly important on the constitutional level), whereas the interest theory becomes more and more important as a constitution becomes more and more of a legal act (rather than a political act). In this context it may be observed that today’s constitutional law seems to be playing a parallel function to 19th-century civil law, and traditional civil law theory seems to be particularly useful in conceptualising contemporary constitutional law constructions, as developed by constitutional courts.